Ecosystem Model on Adaptive MOOC in Higher Education - Ahmad Chafid Alwi; Priyanto Priyanto; Siti Irene Astuti Dwiningrum; Akhsin Nurlaily; Amrih Setyo Raharjo (Jurnal Pendidikan Ekonomi, 2024)
This research aims to develop an adaptive MOOC ecosystem in universities. This study involved development research using the 4-D model, which consists of defining, designing, developing, and disseminating. The results indicate that in developing a MOOC ecosystem, it is necessary to conduct an in-depth analysis of users to find out what structures are needed. The context of MOOCs by companies is undoubtedly different from that of universities. As an educational institution, its stakeholders involve university leaders and researchers from lecturers. In the initial design, it is necessary to test user characteristics so that the MOOC system can make decisions on learning recommendations. We involved metacognitive testing and categorize so that users can learn to the fullest. In its application, validity tests were performed on experts to assess the product from development and on users. The test results showed excellent results. This ecosystem has also been disseminated to users and received a very good response. Moreover, several universities in Indonesia have the status of PTN-BH, which demands financial independence, so MOOC can be one of the breakthroughs to acquire income generation. Keywords: adaptive MOOC, MOOC ecosystem, higher education